HUBUNGAN DUKUNGAN DAN PENDAPATAN KELUARGA DENGAN KUNJUNGAN K4 PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS UJUNG GADING - Radhia, Mekar Zenni; S, Hanifa Zaini.; Asmawati, Dewi; Efiyanti, Efiyanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Antenatal Care (ANC) is a health service that has been provided by health workers for mothers during their pregnancy and carried out in accordance with service standards set out in the Midwifery Service Standards (SPK). The general objective of this study is to find out the factors that influence the low K4 visits of pregnant women at the Ujung Gading Health Center in 2022. This type of research is a quantitative type of research with a cross-sectional approach, namely data collection on the independent variables and the dependent variable is carried out at the same time. The population in this study were all mothers giving birth in October-December 2022 in the Working Area of the Ujung Gading Health Center, a total of 48 mothers giving birth using the total side technique. Data analysis used a test using the Chi-Square test with a 95% degree of confidence with p <0.05. The results of this study are that there is a relationship between the variables of education (p=0.001), Occupation (p=0.038), Parity (p=0.033), Knowledge (p=0.034), Attitude (p=0.039), Distance of residence (p=0.018 ), Family income (p=0.011), Family Support (p=0.001), Health Workers (0.002) with K4 visits to pregnant women in the Working Area of the Ujung Gading Health Center in 2022. The conclusion in this study is that there is a relationship between education, employment, parity, knowledge, attitudes, distance of residence, family income, family support and health workers with K4 visits to pregnant women in the working area of the Ujung Gading Health Center in 2022. The research suggestion is that The health center is even more improving in providing counseling so that the attitude and knowledge of the mother in the K4 examination increases from those who previously did not know to become more knowledgeable.Keywords: ANC, K4Visit, Pregnant Women